Managing risk in disbursement and repayment system of Islamic microfinance service providers: A technological perspective / Nabilah Rozzani - Rozzani, Nabilah (Institute of Graduate Studies, UiTM, 2018)
An urge to cope with globalised environment of banking industry makes it important for Islamic microfinance service providers to seek for new business opportunities. They are therefore vulnerable towards different risks from various sources, which could affect their ability to sustain in the market. Moving forward with vast advancement of technology, many Islamic microfinance service providers have initiated the integration of various innovations to improve risk management. Hence, the current study attempts to seek for qualitative evidences that would explain why and how applications and acceptance of banking technology are changing risk management process for disbursement and repayment system of Islamic microfinance service providers. Comparative case study research method is used to explore risk management processes and implementation of technology for disbursement and repayment system in two types of Islamic microfinance service provider. Qualitative data are collected from observation in client meeting, interview with selected clients and staffs, also documentation obtained from two selected case institutions. Data is then analysed using NVivo 11 to make coding easier and more simplified, as well as to facilitate the process of thematic analysis and pattern matching. From data analysis and findings, it was found that both case institutions of current study appear to be vulnerable towards financial risk, operational risk and strategic risk. Although they were found to have similar risk management process, diffusion of banking technology appears to show different effects in improving risk management…